2016
DOI: 10.1186/s12882-016-0321-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for new-onset diabetes mellitus after living donor kidney transplantation in Korea - a retrospective single center study

Abstract: BackgroundNew-onset diabetes mellitus after transplantation (NODAT) is a serious complication following renal transplantation. The aim of this study was to identify the risk factors for the development of NODAT in Korean transplant patients.MethodsRecipients who underwent living donor kidney transplantation between January 2009 and April 2012 at Asan Medical Center were reviewed. Diagnosis of NODAT was defined according to the American Diabetes Association criteria.ResultsA total of 418 patients were enrolled.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 14 publications
4
25
1
Order By: Relevance
“…N ew-onset diabetes after transplant, or NODAT, is one of the major complications after solid organ transplantation (1,2). There is a five-to six-fold higher incidence of new-onset diabetes mellitus (DM) in the first year post kidney transplantation in comparison to waiting-listed patients (3).…”
Section: Introductionmentioning
confidence: 99%
“…N ew-onset diabetes after transplant, or NODAT, is one of the major complications after solid organ transplantation (1,2). There is a five-to six-fold higher incidence of new-onset diabetes mellitus (DM) in the first year post kidney transplantation in comparison to waiting-listed patients (3).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, incident NODAT directly imposes an extra financial burden on KTRs . Several risk factors for NODAT have been identified thus far, including advanced recipient age, a family history of diabetes, obesity, elevated preoperative fasting plasma glucose (FPG), and chronic exposure to immunosuppressants …”
Section: Introductionmentioning
confidence: 99%
“…5 Several risk factors for NODAT have been identified thus far, including advanced recipient age, a family history of diabetes, obesity, elevated preoperative fasting plasma glucose (FPG), and chronic exposure to immunosuppressants. 6,7 In recent years, considerable attention has been paid to hepatitis viruses, especially hepatitis B virus (HBV) and hepatitis C virus (HCV), as well as their extrahepatic effects on glucose metabolism. Results from the non-transplant population suggested a notable association between HCV infection and diabetes, [8][9][10] but the association between HBV infection and diabetes remained controversial.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies have reported the incidence of PTDM, which was defined by the 2009 KDIGO criteria. In the USA [8] , the incidence of PTDM was reported as 11%, and in Japan [9] and Korea [10] , it was 11.3% and 20.4%, respectively. The prevalence rate in our study, including patients who all came from China, was similar to that in other countries, especially the east Asian countries.…”
Section: Prevalencementioning
confidence: 99%